Sex Differences in Airway Remodeling and Inflammation: Clinical and Biological Factors - Ekpruke, Carolyn Damilola; Silveyra, Patricia (Frontiers in Allergy, 2022)
Asthma is characterized by an increase in the contraction and inflammation of airway muscles, resulting in airflow obstruction. The prevalence of asthma is lower in females than in males until the start of puberty, and higher in adult women than men. This sex disparity and switch at the onset of puberty has been an object of debate among many researchers. Hence, in this review, we have summarized these observations to pinpoint areas needing more research work and to provide better sex-specific diagnosis and management of asthma. While some researchers have attributed it to the anatomical and physiological differences in the male and female respiratory systems, the influences of hormonal interplay after puberty have also been stressed. Other hormones such as leptin have been linked to the sex differences in asthma in both obese and non-obese patients. Recently, many scientists have also demonstrated the influence of the sex-specific genomic framework as a key player, and others have linked it to environmental, social lifestyle, and occupational exposures. The majority of studies concluded that adult men are less susceptible to developing asthma than women and that women display more severe forms of the disease. Therefore, the understanding of the roles played by sex- and gender-specific factors, and the biological mechanisms involved will help develop novel and more accurate diagnostic and therapeutic plans for sex-specific asthma management.